2018
DOI: 10.1097/igc.0000000000001309
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Related Radiation Toxicity Among Cervical Cancer Patients

Abstract: In patients with cervical cancer, radiation toxicity is correlated with lower body mass index, white race, and smoking. Despite technologic advances in radiotherapy planning and delivery, toxicity remains high and interventions to reduce the burden of treatment are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
5
0
3
Order By: Relevance
“…In cervix cancer, Rubinsak et al [35] reported that White women had increased toxicity and considered the effect multifactorial, potentially involving socioeconomic factors, access to care and willingness to seek care for toxicity symptoms. In their cohort, White women were more likely to smoke; smoking is linked with increased toxicity [33,34], probably mediated by vasculotoxic effects exacerbating radiation-induced damage [35]. However, other factors might play a role.…”
Section: Other Cancersmentioning
confidence: 99%
“…In cervix cancer, Rubinsak et al [35] reported that White women had increased toxicity and considered the effect multifactorial, potentially involving socioeconomic factors, access to care and willingness to seek care for toxicity symptoms. In their cohort, White women were more likely to smoke; smoking is linked with increased toxicity [33,34], probably mediated by vasculotoxic effects exacerbating radiation-induced damage [35]. However, other factors might play a role.…”
Section: Other Cancersmentioning
confidence: 99%
“…A sustentação teórica para a análise dos dados foi pautada em resultados de outros estudos relacionados à temática em questão, que abordam os significados e os desconfortos ocasionados pela braquiterapia (7,10,(12)(13)(14)(15)(16)(17)(18)(19) , e na Teoria do Conforto (20) .…”
Section: Métodounclassified
“…Os significados e os desconfortos abrangem as alterações físicas e emocionais decorrentes da doença e tratamento e seus efeitos colaterais (7,10,(12)(13)(14)(15)19) , as incertezas no futuro, as relações de afeto como estímulo ao enfrentamento da doença (7,10) , a religiosidade e a psicologia como suporte emocional (16,17) e o manejo da dor (18) .…”
Section: Métodounclassified
See 1 more Smart Citation
“…The standard of care therapy for cervical cancer is based on combinations of radiation and chemotherapy. These modalities are highly toxic and cause significant morbidity ( 2 , 3 ). Although recent FDA approvals have added immune-based therapy to this armament, cervical cancer lags behind most other cancers in having molecular-based drugs available for therapeutic use.…”
Section: Introductionmentioning
confidence: 99%